Managing Africa’s Natural Resource Endowments: New Dispensations And Good-Fit Approaches - Hanson, Kobena T. (Journal of Sustainable Development Law and Policy, 2025)
Managing a nation’s extractive natural resource endowments can advancenational development if done meaningfully. Unfortunately, across Africa, theapparent mismanagement of such resources, poor growth rates, social tensions,and civil strife in resource-rich countries have thrown up a great deal ofliterature on what is now known as resource curse.It has also ignited calls forenhanced governance and improved capacities for the myriad of actors engagedin natural resource extraction. This article draws on the extant literature tointerrogate the complex entanglements of issues involved in the naturalresource value chain in Africa. It argues that in spite of the general ills,economic challenges, and socio-political pains that resource-rich Africannations face in exploiting and managing their natural resources, the extractiveindustry in Africa is evolving positively, and that the situation of resource-richAfrican states is not immutable. Available evidence suggests that Africa isemerging a new, more complex, participatory, and coordinated vision of NRM;a development that offers opportunities and possibilities for Africa to engageemerging actors especially in the global South. The article concludes thatwhat Africa needs is an approach with a good fit to local realities, and anenhancement of individual and institutional capacities.